Marketing Strategy Analysis of PT. Afra Amanah People (Case Study of Agent in Jabodetabek) - Muhammad Arif, Muhammad Arif (Journal of Entrepreneur and Business, 2023)
PT. Afra Insan Amanah is a form of business entity that brands products for the needs of Muslim children, PT. Afra Insan Amanah uses the name Afrakids in marketing the product. Afrakids in providing the best service to consumers cannot be separated from the help of agents who participate in seizing market potential and at the same time as business partners. The purpose of this study was to determine the external factors and internal factors in the marketing strategy of PT. Afra Insan Amanah with agents in Jabodetabek, to find out SWOT-based marketing strategies for Afrakids agents in Jabodetabek. The sampling technique in this study was non-probability sampling with a purposive sampling type. The sample in this study were 12 Afrakids agents in Jabodetabek. Data collection techniques obtained by interviews, observation and documentation. The results of this study are the formulation of alternative marketing strategies obtained based on external and internal factors, namely maximizing strategic locations, expanding and increasing promotions, deepening relationships with partners, improving good relations with customers, maintaining product quality. Strategies that can be used by Afrakids agents in Jabodetabek based on the SWOT matrix are maintaining and improving product quality, increasing and deepening relationships with resellers. maintain product quality. Strategies that can be used by Afrakids agents in Jabodetabek based on the SWOT matrix are maintaining and improving product quality, increasing and deepening relationships with resellers. maintain product quality. Strategies that can be used by Afrakids agents in Jabodetabek based on the SWOT matrix are maintaining and improving product quality, increasing and deepening relationships with resellers. Keywords :Marketing Strategy, Marketing Mix, SWOT